INFLUENCE OF DRYING ON DOUGLAS-FIR HEARTWOOD IMPREGNABILITY TO WATER (Innovation in Woodworking Industry and Engineering design, 2026)
Within the next ten years, the Douglas-fir will be the main softwood resource harvested in France, largely due to the growing market for wood frame construction in Europe. A large part of this supply will be devoted to EWP production, particularly plywood and LVL. To process these products, bolts must be peeled and therefore require a heat treatment of around 50 °C. Usually, bolts are soaked in hot water for12 to 72 hours, depending on the wood species and bolt diameter. However, Douglas-fir green wood shows two particularities that complicate boil-ing efficiency: (i) the heartwood has a MC near FSP (30 to 40 %) i.e. there is nearly no free water in the tracheid; and (ii) it is impossible to impregnate this heartwood at atmospheric pres-sure with water. As a result, wood material being a very efficient insulator, boiling Douglas-fir prior to peeling for veneer production will take a very long time, since free water is the main medium allowing heat transfer into green wood.This paper includes a review of the anatomical, chemical and physical factors responsible for the very low impregnability of Douglas-fir heartwood. In this analysis, a first set of prelim-inary tests was performed in order to improve impregnation. It consisted of (i) soaking small samples (20 × 20 × 120 mm3 in RTL basis) in hot water at atmospheric pressure at different temperatures (every 10°C between 50 and 90 °C for different treatment durations (5 to 22 hours)); (ii) putting a tensoactive product into water; and (iii) applying ultrasonic waves (200 kHz / 400 W) in order to provoke micro-cavitation and then rupture the bordered pit torus. The results proved the inefficiency of such treatments on Douglas-fir impregnability, even on small samples. A second set of tests was conducted to quantify the influence of extractives and of drying (heating, vacuum) under the FSP on heartwood permeability. If extractives do not appear to have a real impact, then drying treatment will also not greatly improve permeability. One of the hypotheses is that the drying process may have caused micro cracking in the cell walls.Other tests are in progress to quantify the speed of absorption of liquid in both longitudinal and transverse directions.